2011
DOI: 10.1080/03075070903519210
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the combined relationships of student and teacher factors on learning approaches and self‐directed learning readiness at a Malaysian university

Abstract: This article presents the findings of a study of the interrelationships between students' individual characteristics, self-efficacy beliefs, parental involvement, university and classroom learning environments; teachers' individual characteristics, teaching efficacies, university and classroom learning environments, teacher outcomes and approaches to teaching; and approaches to learning (deep and surface learning) and self-directed learning readiness. The study was guided by a two-level integrated theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 58 publications
1
27
0
1
Order By: Relevance
“…Research has continuously reported that students’ approaches to learning are associated with learning outcomes [68]. Snelgrove and colleagues reported that student nurses’ deep approaches to learning sociology were positively associated with their learning outcome as indicated by grade point average (GPA) and sociology exam results [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has continuously reported that students’ approaches to learning are associated with learning outcomes [68]. Snelgrove and colleagues reported that student nurses’ deep approaches to learning sociology were positively associated with their learning outcome as indicated by grade point average (GPA) and sociology exam results [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also consistently shown that learning approaches of students are associated with learning outcomes (Kek et al, 2007;Kek and Huijser, 2011;Trigwell and Prosser, 1991;Van Rossum and Schenk, 1984). Ramsden (1992, p. 59) summed up the powerful relationships between learning approaches and learning outcomes as follows: "surface approaches are usually more strongly linked to poor learning than deep ones are to effective learning, and the connections between grades and learning approaches are less marked than those between measures of learning quality and approaches".…”
Section: Approaches To Learningmentioning
confidence: 99%
“…The focus of this paper is to explore what group work characteristics activate deeper approaches to learning. approaches to learning then this had a statistically significant and direct influence on their readiness for self-directed learning (Kek and Huijser, 2011). Being an effective group member often begins with individual processes, which extend towards group processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations